Report on research, innovation and technological performance in Germany 2022 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2022)
[Foreword ...] In the A chapters, the Commission of Experts addresses R&I policy in the new legislative period. In chapter A 0, it advocates developing a new, comprehensive research and innovation strategy based on the experiences of the High-Tech Strategy and making the necessary investments for the future. In chapter A 1, the Commission of Experts discusses how to create stronger incentives for the development and diffusion of low-carbon technologies. It attaches particular importance to CO2 pricing. Based on the observation that Germany is lagging behind in key digital technologies, the Commission of Experts emphasises in chapter A 2 the need to further promote research and innovation activities in this area, to drive forward the expansion of the digital infrastructure and to exploit the innovation and value creation potential of data. Chapter A 3 deals with strengthening the skilled labour supply through education and qualification. The Commission of Experts emphatically points out that to ensure a good supply of suitably qualified workers, schools and universities as well as vocational and continuing education and training must become more efficient, more needs-based and more socially permeable. Chapter A 4 discusses how the existing downward trend in the innovator rate can be counteracted. In this context, the Commission of Experts advocates improving the conditions for start-ups and focusing research and innovation funding on potential. In chapter A 5, the Commission of Experts proposes adapting existing governance structures, promoting agile policy action and integrating policy learning more firmly into existing processes. Key enabling technologies unlock high potentials for a prosperous technological and economic development of a national economy. They are of vital importance for current and future value creation activities. In chapter B 1, the Commission of Experts concludes that Germany has strengths in the key enabling technology areas of production technologies as well as bio- and life sciences. In the area of digital technologies, however, Germany and the EU 27 show clear weaknesses. This means that they are not only losing touch in a technology area that is becoming increasingly important economically but are also jeopardizing their existing strengths in production technologies as well as in the bio- and life sciences, which are increasingly being penetrated by digital technologies. According to the Climate Protection Act, Germany must become climate neutral by 2045. In chapter B 2, the Commission of Experts analyses the role of private motorized transport in reducing greenhouse gas emissions. At the vehicle level, a reduction of these emissions can be achieved using new drive systems and alternative fuels. The Commission of Experts therefore recommends reducing the attractiveness of conventional internal combustion vehicles by means of a sufficiently high CO2 price. In addition, the system of taxes and charges for passenger cars should be reformed and directly aligned with the use of passenger cars. As developments in autonomous driving create opportunities for bundling transport, the legal framework for passenger transport should not hinder the development of these innovative mobility services. In chapter B 3, the Commission of Experts analyzes the effects that the use of digital B2B platforms can have on companies' innovation activities and the challenges that companies face when using them. Companies see many advantages of B2B platform use for their own innovation activities, for example through simplified access to data and the integration of external partners in the innovation process. At the same time, they have concerns about data protection and IT security and fear the outflow of knowledge relevant to innovation and competition. To leverage the potential associated with digital B2B platforms, the Commission of Experts recommends improving the conditions for data-based B2B business models and pushing for uniform platform regulation across the EU. In chapter B 4, the Commission of Experts addresses the digitalization of the healthcare system, which is associated with great potential for innovation and value creation with regard to better quality and more efficient healthcare. In particular, the increasing availability of health data in combination with new digital analysis methods creates opportunities for more personalized diagnostics and treatment. In international comparison, Germany lags far behind other European countries in the digitalization of the healthcare system. To remove existing obstacles and to be able to leverage the innovation potential associated with digitalization, a digitalization strategy is needed, as well as a coordinating body with the broadest possible enforcement powers for its implementation.
Keywords: 330